Co-creation and Evaluation of Nationwide Remote Training Service for Mental Health Education of Community Health Workers in Rwanda - Annik Willems; Jean-Damascène Iyamuremye; Claire Nancy Misage; Virginia Smith-Swintosky; Yvonne Kayiteshonga (Frontiers Media S.A., 2021)
Objective: Johnson & Johnson Global Public Health and the Ministry of Health of Rwanda strengthened the mental health awareness by providing an innovative, low-cost, easily accessible, and scalable remote training service (RTS) on mental health for Community Health Workers (CHWs).Methods: The RTS consisted of eight training modules shared via simple feature phones over a 4-week period. Quiz questions and baseline/endline assessments were included to assess the feasibility and acceptability of the training platform, the knowledge and self-confidence gained by the CHWs, and prospects for the sustainability of the platform.Results: Ninety-three percent of the CHWs completed at least four of the eight training modules, and 42% of the CHWs improved with a higher end score. The training content was considered interesting, easy to understand, and helpful to intervene appropriately to refer patients with signs of mental illness to a hospital and to provide community and family education on mental health topics.Conclusion: The RTS is feasible and acceptable for the delivery of mental health training on a large scale and contributed to strengthening the capacity in delivering mental health care at community level.